2019
DOI: 10.1186/s12864-019-5813-z
|View full text |Cite
|
Sign up to set email alerts
|

Mapping gastrointestinal gene expression patterns in wild primates and humans via fecal RNA-seq

Abstract: Background Limited accessibility to intestinal epithelial tissue in wild animals and humans makes it challenging to study patterns of intestinal gene regulation, and hence to monitor physiological status and health in field conditions. To explore solutions to this limitation, we have used a noninvasive approach via fecal RNA-seq, for the quantification of gene expression markers in gastrointestinal cells of free-range primates and a forager human population. Thus, a combination of poly(A) mRNA enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…Isolation of mRNA from total fecal RNA may improve the sensitivity of the RT-qPCR analysis since we have previously [ 86 ] observed that total fecal RNA contains a significant amount of bacterial RNA and this has been confirmed via RNA-seq data in primates [ 89 ]. In Fig.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Isolation of mRNA from total fecal RNA may improve the sensitivity of the RT-qPCR analysis since we have previously [ 86 ] observed that total fecal RNA contains a significant amount of bacterial RNA and this has been confirmed via RNA-seq data in primates [ 89 ]. In Fig.…”
Section: Introductionmentioning
confidence: 94%
“…The intestinal epithelial cells act as a barrier against pathogens, and the daily shedding of these cells into feces has been used in rodents and humans as a source of RNA to evaluate gene expression in the gastrointestinal tract (GIT) [ 88 ]. This method has also been used to find transcriptomic similarities in the GIT between humans and wild primates [ 89 ]. Using a similar approach, RNA was isolated from fecal samples that our group refer to as “fecal RNA” from neonatal dairy calves [ 86 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations